Processes and control systems: synthesis, modeling, optimization - Krasnikov, I.; Babichenko, A.; Krasnikov, I.; Babichenko, J.; Dzevochko, O.; Kravchenko, Y.; Lysachenko, I.; Samsonkin, V.; Druz, V.; Yurchenko, O.; Budashko, V.; Glazeva, O.; et al. (TECHNOLOGY CENTER PC, 2025)
The collective monograph is devoted to the study of modern approaches to modeling, optimization and in- creasing the efficiency of control systems in complex technical complexes. The presented material covers is- sues of heat and power processes, operational data analytics, optimal regulation of mobile power plants, intel- ligent local power grids and digital monitoring of industrial equipment. The focus is on methods of identifying uncertainties, implementing adaptive algorithms, using mathematical models and three-dimensional control technologies. The monograph demonstrates the interaction of theoretical principles and applied solutions, reflecting the transition of engineering systems from static structures to dynamic objects with built-in mecha- nisms of self-diagnosis and optimization. The work summarizes tools that contribute to the formation of a new technical paradigm based on the integration of modeling, control and predictive analysis.